Anxiety level differentiation in 6-12 years old children before and after loss dental care using topical anasthesy at Dental Hospital Hasanuddin University - Adam M. Hamudeng; Fynna R. Ryanda (DiscoverSys Inc., 2016)
Anxiety is a psychological and physiological condition which signed by emotion, cognitive, and someone’s behavioral component. Anxiety behavior has long been recognized as the most difficult aspect in the management of patients and may frustrate a dental treatment that will be carried out, especially in children ages 6-12 years. Fear of treatment tooth extraction and local anesthesia is the main reason for kids disliking dental care. This type of research is observational analytic with nonprobability sampling technique, because this study used a population of pediatric patients who visited the location of the research that has been determined. Total sample of this research are 30 people who fulfill the criteria. The sample consist of 16 boys and 14 girls with age range of 6 to 12 years old. The level of anxiety before and after tooth extraction assessed using Facial Image Scale (FIS). Facial Image Scale (FIS) has five criteria which describe the level of anxiety in children, very happy by point 1, happy by point 2, normal by point 3, unhappy by point 4, and very unhappy by point 5. The results of the analysis of differences in anxiety with FIS measurement tools show there are differences in the level of anxiety in children before and after tooth loss based on the location of the jaw, the type of anesthesia applied topically, gender, and overall. Overall, there is a difference in children before and after tooth loss and the difference is significant